STUDI KELAYAKAN USAHA KOPRA DI DESA SRIBATARA KECAMATAN LASALIMU KABUPATEN BUTON - Edy, Safrin (Program Studi Agribisnis, Fakultas Pertanian, Universitas Muhammadiyah Buton, 2017)
The purpose of this study was: 1) To find out the amount of income received by farmers from copra business in Sribatara Village, Lasalimu Sub-district, Buton Regency; 2) To find out the value of the feasibility of copra business in Sribatara Village, Lasalimu Sub-district, Buton Regency. This research was carried out in Sribatara Village, Lasalimu Sub-district, Buton Regency, from June to July 2017. The technique of determining the sample in this study was conducted by the census (sampling saturated) as many as 20 copra farmers. Based on the results of the study and discussion showed that the income of copra business farmers in Sribatara Village, Lasalimu Subdistrict, Buton Regency, was 13,538,537 per year. Furthermore, the results of the feasibility analysis of copra business were obtained with average revenue of IDR 17,204,000, -per year, - while the average total cost is IDR 3,665,463 per year and has an R/C ratio of 4.69. This snows that each cost is IDR 1 then provides revenue of IDR 4.69.   Keywords: Farming Analysis, Copra, Farming Feasibility